Experimental evaluation of the influence of crankshaft rotation frequency on the amplitude of pressure pulsations in gas communications of low-flow reciprocating compressors - S. S. Busarov; A. V. Nedovenchany; K. A. Bakulin; N. G. Sinitsin; A. A. Panyutich (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The presence of gas pressure pulsations in the suction and discharge pipes of reciprocating compressors is associated with their periodic connection and disconnection from the working chamber during the operation of self-acting valves. The present work is devoted to the development of a methodology for experimental investigation of pressure pulsations in gas communications of reciprocating compressors under various operating modes in relation to an existing laboratory installation and comparison of the results obtained with the results of calculations obtained on the basis of the use of well-known repeatedly tested techniques. This proven technique can be used to study pressure pulsations in gas communications of a wide class of low-flow reciprocating compressors.